Conductivity of layered structures with a strongly degenerate electron gas - Petrov, P.P. (Condensed Matter Physics, 1999)
The conductivity of periodical multilayer structures with a degenerate electron gas is calculated. It is shown that for smooth tunnelly transparent barriers the resistivity of structure coincides with the corresponding value of
the bulk material. In the presence of a random potential at the interface
between the layers, the conductivity of the system decreases with the increase of a ratio of the mean free path to the period of the structure. Обчислена електропровiднiсть перiодичних багатошарових структур
з виродженим електронним газом. Показано, що для гладких тунельно прозорих бар’єрiв опiр структури спiвпадає з вiдповiдним значенням для об’ємного матерiалу. У випадку, коли на границях роздiлу iснує випадковий розсiюючий потенцiал, провiднiсть системи зменшується зi збiльшенням вiдношення довжини вiльного пробiгу електронiв до перiоду структури.